Biocompatibility and Angiogenic Effect of Chitosan/Graphene Oxide Hydrogel Scaffolds on EPCs. (19th May 2021) - Zhang, Lifang; Li, Xinping; Shi, Congying; Ran, Gaoying; Peng, Yuting; Zeng, Shuguang; He, Yan
Abstract : Angiogenesis in the field of tissue engineering has attracted significant attention. Graphene oxide has become a promising nanomaterial in tissue engineering for its unique biochemical properties. Therefore, herein, a series of chitosan (CS)/graphene oxide (GO) hydrogel scaffolds were synthesized by crosslinking CS and GO at different concentrations (0.1, 0.5, and 1.0 wt.%) using genipin. Compared with the CS hydrogel scaffolds, the CS/GO hydrogel scaffolds have a better network structure and mechanical strength. Then, we used endothelial progenitor cells (EPCs) extracted from human umbilical cord blood and cocultured these EPCs with the as-prepared scaffolds. The scaffolds with 0.1 and 0.5 wt.%GO showed no considerable cytotoxicity, could promote the proliferation of EPCs and tube formation, and upregulated the expressions of CD34, VEGF, MMP9, and SDF-1 in EPCs compared to the case of the scaffold with 1.0 wt.%GO. This study shows that the addition of graphene oxide improves the structure of chitosan hydrogel and enhances the proliferation activity and angiogenic capacity of EPCs.